Integration of microRNA–mRNA profiles and pathway analysis of plant isoquinoline alkaloid berberine in SGC-7901 gastric cancers cells - Yang YH; Zhang N; Li KD; Chen J; Qiu L; Zhang JF (Dove Medical Press, 2018)
Yanhong Yang,1 Na Zhang,2 Kundong Li,2 Juan Chen,2 Lang Qiu,1 Jufeng Zhang2 1The First Affiliated Hospital, School of Clinical Medicine, Guangdong Pharmaceutical University, Guangzhou, People’s Republic of China; 2School of Life Science and Biopharmacology, Guangdong Pharmaceutical University, Guangzhou Higher Education Mega Center, Guangzhou, People’s Republic of China Purpose: Berberine (BBR) is a traditional Chinese medicine normally used for gastroenteritis, and recent research found that it could fight against tumors. In this study, we focused on integrating miRNA sequencing and RNA sequencing of SGC-7901 gastric cancer cells treated by BBR to elucidate their underlying mechanisms. Materials and methods: WST-1 assay and flow cytometry were used to check the effects of BBR on SGC-7901. miRNA sequencing and RNA sequencing were used to establish the miRNA and mRNA profiles of BBR-treated SGC-7901. Results: The results showed that BBR could inhibit the proliferation of SGC-7901 cells and induce G1 arrest in cell cycle phase and apoptosis. A total of 1,960 upregulated genes and 4,837 downregulated genes were identified in the RNA sequencing and 347 upregulated and 93 downregulated miRNAs in the miRNA sequencing. A total of 78 novel miRNAs were also found. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analysis showed that the genes were related to pathways in cancer and metabolism. We also analyzed the miRNA–mRNA network of genes grouped into cell cycle, apoptosis, inflammation, metabolism, cell junction, acetylization process, TGF-β pathway, and Wnt signaling pathway. Conclusion: BBR could inhibit the proliferation of SGC-7901 cells and induce apoptosis. Integrated analysis of microRNA–mRNA profiles is a promising approach to validate gene expression patterns associated with malignant phenotype and study the mechanisms of anticancer. Keywords: berberine, gastric cancer, RNA sequencing, microRNA sequencing, integrated analysis